Decolonisation of history assessment: An exploration - Godsell, S. D. (South African Journal of Higher Education, 2021)
Although assessment forms a key part of knowledge production in Higher Education spaces, it is rarely brought into the decolonisation conversation. Assessment performs a crucial inclusion/exclusion function. As this function determines formalised recognition of knowledge and proficiency, decolonisation of assessment should be part of decolonial research in Higher Education. Assessment outcomes determine whether and when students will progress and graduate If we focus solely on decolonising pedagogy and content, but rely on existing assessment practises, decolonisation stops at precisely the moment in which students’ knowledge is measured. This article explores decolonising assessment through conceptual research and a case study using assessments and discussions from three History courses in a teacher education programme. This combination allows for the blending of a theoretical approach with some aspects of application, as well as a grounding in student-driven ideas. The case-study data is drawn from class discussions.1 This article brings together principles of assessment, theories of teaching History, and theories of decolonisation. I examine how assessment can disrupt notions of where knowledge is held, built, and displayed. I also try to understand what kinds of assessment students could experience as enabling rather than gate-keeping. This investigation is exploratory, with the aim of opening a field of enquiry, not providing clear and definitive answers. However, as students pass through classrooms each year, there is an urgency to the enquiry. How these questions are approached day to day in the classroom will inform both findings and questions.